One Basket - Ferber, Edna, 1885-1968 (Salt Lake City, UT : Project Gutenberg, 1996)
"One Basket" by Edna Ferber is a collection of short stories written in the early 20th century. The opening stories focus on the characters and challenges faced by women in a small-town American setting, exploring themes of identity, societal expectations, and personal transformation. The narratives often revolve around the lives of female protagonists, such as Blanche Devine, who struggle to redefine themselves in environments that have predefined roles and judgments. The opening of "One Basket" introduces readers to the life of Blanche Devine, a woman seeking redemption in a small town after a past defined by scandal and reputation. As she attempts to assimilate into the community by buying a respectable house and adopting a more conventional lifestyle, the opposing reactions of her neighbors highlight the challenges she faces. Despite her efforts to foster a sense of belonging, she remains an outsider, demonstrating the complexities of reintegrating into society and facing the weight of public scrutiny. The narrative sets the tone for the entire collection, emphasizing the intricate lives and emotional landscapes of Ferber's characters. (This is an automatically generated summary.)
The woman who tried to be good -- The gay old dog -- That's marriage -- Farmer in the dell -- Un morso doo pang -- Long distance -- The maternal feminine.
Release date is 1996-04-01
Produced by Charles Keller. HTML version by Al Haines.
Keywords: Short stories; United States -- Social life and customs -- 20th century -- Fiction